Communication a post-discipline - Waisbord, Silvio R. (Silvio Ricardo) 1961- (Polity Press, 2019)
"Communication studies is a fragmented field. As a result of its roots in various disciplinary traditions, it is built on fluid intellectual boundaries. Should we worry about this state of dispersion? Waisbord argues that it is impossible to transcend fragmentation, but communication studies is better served by accepting and stimulating differences"--Provided by publisher.